A REMARK AND AN IMPROVED VERSION ON RECENT RESULTS CONCERNING RATIONAL FUNCTIONS - Nirmal Kumar Singha; Barchand Chanam (Ural Mathematical Journal, 2025)
This paper extends as a lemma an auxiliary result obtained by Singh and Chanam. Using it, we prove a refinement of the Turán-type inequality for rational functions obtained recently by Akhter et al.  Next, using examples, we discuss the result of Mir et al.